Saussure and its cultural environment The dialectic of extension and rupture (Linguist, 2021)
This article links the thought of de Saussure to the historical context and the general cultural environment in which this thought developed, and attempts to review the various general trends that prevailed in the second half of the 19th century, and that constituted important sources of the theory of de Saussure. We adopt in this article that Human thought, is subject to the dialectic of extension and Epistemological estrangement.     Saussure had a wide knowledge of comparative anatomy, geology, social sciences, philosophy, psychology, and other sciences that have directly influenced linguistic thought in general, and saussurian linguistics in particular.     In addition, his cultural environment also had a positive role in helping him to build his theory. Saussure was a temporary of great linguists such as Boas, Otto Jespersen Paul Passy, ​​ Sigmund Freud, Emile Durkhelm, Henry Bergson and other thinkers who had a direct influence and whose ideas were background adopted by Saussure in establishing his theory and methodology and in proposing a set of Important concepts.
Keywords: cultural paradigm; universal system of language; General Linguistics; vowels; diachronic; synchronic; linguistic sign; arbitrary; value; Historical Linguistics; Descriptive Linguistics